Grid connection approach for very small-sPico-hydro systems using PV microinverters - Ribeiro, Gabriela Moreira (2020)
The use of renewable energy sources has grown significantly in recent decades, with emphasis on resources that have a low environmental impact in the energy production process. Small-scale pico-hydro systems have great potential and are also in line with increasing environmental requirements. Microgrids can integrate this type of solution into self-supporting systems and electrification of remote locations. This paper presents and discusses an approach for very small-scale pico-hydro systems, up to 300W, for grid connection, using photovoltaic microinverters recently launched on the market. Experimental validation was performed on a test workbench and a laboratory platform. The results were carried on applying different input power values. The laboratory platform consists of a water wheel prototype with specific water flow and head. Data from two generators, three microinverters, and a passive load were collected during the laboratory experiments. This approach presents encouraging results for the exploration of the emerging energy potential of pico-hydro systems of very small pico-hydro systems, with power available 24 hours per day. This work is a contribution to the dissemination of this approach, which can be easily widespread and contribute to environmentally friendly energy production.